SISTEM INFORMASI PEMETAAN POTENSI SUMBERDAYA ALAM - Dedi Irawan; Adi Gustian (Jurnal Ilmiah Matrik, 2019)
Penukal Abab Lematang Ilir Regency is one of the regencies in southern Sumatra that has abundant natural resources such as oil, natural gas and coal which reach 76.12% per year of total revenue in various sectors. The following table is the sub-district natural resources in the Penukal Abab Lematang Ilir Regency, As a newly established district, the new autonomous region, Penukal Abab Lematang Ilir still has many shortcomings, both in human resources, community governance and technology as a means of supporting work activities in the district This, including one of the technologies for discovering natural resources in the earth, Penukal Abab Lematang Ilir Regency as a government asset, is currently still being done manually both in terms of monitoring and storing data, making it less efficient in reading accuracy. As a solution, a natural resource potential mapping information system was created. Penukal Abab Lematang Ilir District used the action research method and ArcGis software.